Isolation of Pasteurella haemolytica from the nasal cavity of goats. - Sabri, Jasni; Saad, Mohd Zamri; Mutalib, Abdul Rahim; Abdul Rahman, Sheikh Omar (W.B. Saunders, 1991)
Twenty transport-stressed goats were divided into two groups. The first group was further stressed with steroid. Pasteurella haemolytica was found at various sites in the nasal cavity of goats in this group as early as 2 weeks post-transportation. The successful isolations continued consistently with more goats having pure growth of P. haemolytica at later stages. Mild catarrh rhinitis, loss of epithelial cilia and erosions were the main lesions observed in the nasal cavity. Goats in the second group that were not given steroid injections had inconsistent bacterial isolation and less severe pathological lesions.